American BRCA Outcomes and Utilization of Testing (ABOUT) Study: A Pragmatic Research Model that Incorporates Personalized Medicine/Patient‐Centered Outcomes in a Real World Setting. Issue 1 (12th September 2014) - Armstrong, Joanne; Toscano, Michele; Kotchko, Nancy; Friedman, Sue; Schwartz, Marc D.; Virgo, Katherine S.; Lynch, Kristian; Andrews, James E.; Aguado Loi, Claudia X.; Bauer, Joseph E.; Casares, Carolina; Teten, Rachel Threet; et al.
Abstract: Research to date regarding identification and management of hereditary breast and ovarian cancer syndrome (HBOC) in the U.S. has been confined primarily to academic center‐based studies with limited patient engagement. To begin to understand and address the current gaps and disparities in delivery of services for the appropriate identification and optimal risk management of individuals with HBOC, we designed and have initiated the American BRCA Outcomes and Utilization of Testing (ABOUT) Study. ABOUT relies on a collaborative patient advocacy, academic and industry partnership to recruit and engage U.S. individuals who are at increased risk for HBOC and investigate their experiences, decisions and outcomes. It utilizes an extensive research infrastructure, including an interactive web‐based data system and electronic interfaces for secure online participation and automated data exchange. We describe the novel recruitment approach that was designed for collaboration with a national commercial health plan partner to identify all individuals for whom a healthcare provider orders a BRCA test and mail to each individual an invitation to participate and study packet. The study packet contains detailed information about the study, a baseline questionnaire and informed consent for participation in the study, for release of relevant medical and health plan records and for ongoing research engagement. This approach employs patient‐reported, laboratory‐reported and health plan‐reported outcomes and facilitates longitudinal engagement. We believe that the type of innovative methodology and collaborative framework we have developed for ABOUT is an ideal foundation for a patient‐powered research network. This approach can make substantial contributions to identifying current and best practices in HBOC, leading to improved strategies for clinical care and optimal health outcomes among individuals with high inherited risk for cancer.